Differential Expression of Extracellular Matrix Components in the Fallopian Tubes Throughout the Menstrual Cycle - Cardenas-Sankan, G; Orihuela-Diaz, P; Diaz-Saldivar, P; Velasquez, L (2012)
Sin Editorial Disponible